Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

By factor theorem,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,
Put y = 1 we get 2+1-2-1=0 =>!(y-1) is the factor of the given equation now divide the equ by y-1 we get 2y^2 -3y+1 ,,,,,,,,,,,,,,,,
now again using factor theorem put y=1 we get 2 -3+1 =0 => (y-1) is the factor of 2y^2-3y+1 divide it by (y-1) we get 2y-1 so the equ become (y-1)(y-1)(2y-1)